Impact analysis of fibreglass reinforced composites - Zakaria, Kamarul Ariffin (2006)
Fibreglass reinforced composites are being used in various applications due to excellent mechanical properties especially high strength to weight and high stiffness to weight ratio. However, in laminated structures they are very susceptible to impact loading due to laminar system with weak interface. The damaged of composites structures under impact load is one of the most important aspect of their behavior in applications. The aim of this project is to study the effects of low velocity impact on composite structures. Finite element models for cases of impact on fibreglass reinforced composites were built using MSC.Patran and solved using LS-DYNA software. The results obtained were correlated with experimental test results done previously. Once the correlation was established, several finite element models were created under various loading conditions to study the behaviour of composites under impact loading. Among the parameters studied were the effects of impactor velocities, impactor masses, ply-orientations, impactor shapes and impact angles.